Sharia (Islamic Law) Perspectives of COVID-19 Vaccines - Mardian, Yan; Shaw-Shaliba, Kathryn; Karyana, Muhammad; Lau, Chuen-Yen (Frontiers in Tropical Diseases, 2021)
The Coronavirus disease 2019 (COVID-19) pandemic has caused health, economic, and social challenges globally. Under these circumstances, effective vaccines play a critical role in saving lives, improving population heath, and facilitating economic recovery. In Muslim-majority countries, Islamic jurisprudence, which places great importance on sanctity and safety of human life and protection of livelihoods, may influence vaccine uptake. Efforts to protect humans, such as vaccines, are highly encouraged in Islam. However, concerns about vaccine products' Halal (permissible to consume by Islamic law) status and potential harm can inhibit acceptance. We herein explain the interplay between Sharia (Islamic law) and scientific considerations in addressing the challenge of COVID-19 vaccine acceptance, particularly in Muslim populations.